A Systematic Literature Review(Slr) On The Utilizationof Ultra-High Performancefibre-Reinforced Concrete(Uhpfrc) For Repair And Strengthening Application - Hakim, Raul (Universiti Sains Malaysia, 2022)
This dissertation presents a systematic literature review about the utilisation of ultra-high-performance fiber-reinforced concrete (UHPFRC) to repair and strengthen damaged concrete . There are two objectives of this review. First is to identify the different cases of concrete deterioration and the corresponding utilization of UHPFRC in the repair and strengthening applications. The next objective is to compare and assess the effectiveness of the use of UHPFRC in different repair and strengthening applications based on the available literatures. UHPFRC is a cementitious composite that has compressive strength higher than 150 MPa. The high strength of the concrete is thanks to its high cement content, making it suitable to be used as repair material. From the Scopus database, there were 12 articles that had been identified for this review. Systematic searching strategies was used to filter out irrelevant articles and the articles are filtered again through quality assessment to further remove low quality articles. In this review, the usage of UHPFRC that is used to repair different cases of concrete deterioration were discussed. From the articles reviewed, it showed that UHPFRC is already widely used for treating concrete damaged by corrosion, cracking and ASR. Also, various kind of methods were used to apply the UHPFRC onto the damaged concrete. Based on the studies reviewed, the effectiveness of the repaired concrete was found to be acceptable. Although UHPFRC have high compressive strength, the selection of repair material should be based on the deformation mechanism, site condition, and client requirement because different repair materials come with different advantages and disadvantages. Knowing these properties should be helpful to decide the most suitable material needed for repair works.